Towards a biorefinery processing waste from plantain agro-industry: process design and techno-economic assessment of single-cell protein, natural fibers, and biomethane production through process simulation - Gómez, James A. (2022)
The plantain agro-industry generates different residues in the harvest and post-harvest stages. Therefore, the design of processes for valorization is required. The aim of this work was to design and techno-economically evaluate the processes for the production of single-cell protein, natural fibers, and biomethane from plantain residues by process simulation in the framework of the design of a future biorefinery for valorization of these residues. The processes were simulated using SuperPro Designer. The scale size was calculated at 1,267,071 tons for the processing of plantain lignocellulosic waste (pseudostems) and 3179 tons for the processing of starchy waste (rejected unripe plantain fruits). The results obtained suggest that the best alternative for the valorization of plantain residues corresponded to the production of natural fibers, with a net present value of $29,299,000. This work shows that waste from the plantain agro-industry exhibits high potential as a feedstock for the production of value-added products. In addition, the process flowsheets simulated in this work can be integrated into the basic design of a biorefinery processing plantain waste.